The eleventh commandment - Archer, Jeffrey, 1940- (London : Harper Collins Publishers, 1998)
In Russia to assassinate a presidential candidate, a CIA agent is betrayed by his director who wants to eliminate a man who knows too much. But Connor Fitzgerald will escape from jail and obtain his revenge.
Contents of this book vary slightly from the book of the same title published in the same year.
Keywords: Intelligence officers -- Fiction; Americans -- Russia -- Fiction; World politics -- Fiction; Assassins -- Fiction; Russia -- Fiction